EVALUASI IMPLEMENTASI APLIKASI EMIS (EDUCATION MANAGEMENT INFORMATION SYSTEM) STUDI MULTI KASUS PADA MADRASAH IBTIDAYAH SWASTA ATTAQWA PANAIKANG KOTA MAKASSAR DAN MADRASAH IBTIDAYAH SWASTA KARAMA KABUPATEN BULUKUMBA) - Nhabila Putri; Muh. Ardiansyah; Ansar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Nhabila Putri. 2026. Evaluation of the Implementation of the Education Management Information System (EMIS): A Multi-Case Study at Attaqwa Panaikang Private Islamic Elementary School in Makassar City and Karama Private Islamic Elementary School in Bulukumba Regency (supervised by Muhammad Ardiansyah and Ansar). This study aims to evaluate the implementation of the Education Management Information System (EMIS) as a school management information system at Attaqwa Panaikang Private Islamic Elementary School in Makassar City and Karama Private Islamic Elementary School in Bulukumba Regency, as well as to analyze the supporting and inhibiting factors in its implementation. This study uses a descriptive qualitative approach with a multi-case study design. Data collection techniques include observation, interviews, and documentation, with data validity tested through triangulation of sources, techniques, and time. Data analysis uses the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. The implementation evaluation is conducted using the CIPP model (Context, Input, Process, Product). The results show that the implementation of EMIS in both madrasahs has been carried out well in supporting administrative processes and data reporting. Attaqwa Panaikang demonstrates more optimal implementation due to adequate infrastructure, competent operators, and a structured work system, thereby improving efficiency and data accuracy. Meanwhile, Karama continues to implement EMIS despite facing challenges such as limited internet access, equipment, and human resource training. Supporting factors include the commitment of the principal, compliance with policies, and collaboration between teachers and operators, while inhibiting factors include limited infrastructure, uneven information technology competence, and operator workload. Overall, EMIS improves administrative order, but its utilization remains limited to administrative aspects and has not been fully optimized as a basis for data-driven decision making.